Review of tensairity and its applications in agricultural aviation - Zang, Ying; Xiuyan, Gu; Zhiyan, Zhou; Xiwen, Luo; Yu, Zang; Xingyuan, Qi; Wulan, Liu; Cheng, Yang (International Journal of Agricultural and Biological Engineering, 2016)
In recent years, the unmanned aerial vehicle (UAV) has undergone rapid development in field of agricultural plant protection; however, the payload and max-endurance are bottlenecks that limit its further development. Tensairity is a new structure consisting of a bag filled with low-pressure gas, an upper rigid rod and a lower flexible cable. It puts tension pressure on the whole structure through internal gas pressure, provides continuous support to the upper rigid rod, and that is to say, the tensairity improves the stability of the structure in some way. And also, tensairity is a self-supporting and self-balancing system, which means it is a simple, lightweight structure with small storage volume, strong bearing capacity, and low engineering cost. It also has the advantages of gasbag and BSS (beam string structure). The main objective of this research was to introduce the theoretical basis of tensairity and then discussed its development and applications. Moreover, the advantages and disadvantages of tensairity were summarized, and development prospects of tensairity in agricultural aviation were presented. At last, it can be concluded that tensairity has potentials in agricultural aviation. If tensairity is applied in agricultural UAVs, it will solve the two major problems of payload and max-endurance better, and help promoting the development of agricultural aviation technology in agricultural aviation administration and application. Also, it will help with meeting the aerial application requirements of high efficiency and maximal environmental protection. This research will provide a reference for improving working efficiency and economic benefits of UAVs in agricultural plant protection.Keywords: tensairity, agricultural aviation, unmanned aerial vehicle (UAV), bionics, numerical simulation, payloadDOI: 10.3965/j.ijabe.20160903.2510Citation: Zang Y, Gu X Y, Zhou Z Y, Luo X W, Zang Y, Qi X Y, et al. Review of tensairity and its applications in agricultural aviation. Int J Agric & Biol Eng, 2016; 9(3): 1－14.